Model Investasi Kotor Pada Respon Penawaran Petani Tanaman "Cassiavera" di Sumatera Barat - Idrus, Rusda Khairati (Jurnal Ekonomi, 2012)
Plantation subsector is contributed to National Gross Domectic Product and in agricultural sector, also in Product Domestic Regional Bruto of West Sumatera components. In West Sumatera, cassiavera is a spesific comodity which contributed to PDRB and implemented by RPMD. This paper will explain how cassiavera cultivator in plantation determined by gross investment with responses in a model of supply cassiavera in West Sumatera. This model used to identify the influence factors in responses cassiavera farming. Overall, this paper have conclution that chhoosing model to identify the influence factors in responses cassiavera farming consist of three factors: growing location of plant characteristic, data existing, and estimated method. The important factor which is recomended to determine supply of cassiavera farming in West Sumatera consist of economic factor, selling price of cassiavera, coffe and rice price as a competitive product in land uses. Meanwhile, non economic factor also in important recomendation are climate change and temperature.